Pre-emptive Intervention for Autism Spectrum Disorder: Theoretical Foundations and Clinical Translation - Douglas, Pamela S. (Frontiers in Integrative Neuroscience, 2019)
Autism Spectrum Disorders (ASD) are an emergent public health problem, placing significant burden upon the individual, family and health system. ASD are polygenetic spectrum disorders of neural connectome development, in which one or more feedback loops amplify small genetic, structural, or functional variations in the very early development of motor and sensory-motor pathways. These perturbations trigger a ‘butterfly effect’ of unpredictable cascades of structural and functional imbalances in the global neuronal workspace, resulting in atypical behaviours, social communication, and cognition long-term. The first 100 days of life are critically neuroplastic and comprises an injury-sensitive developmental window, characterised by a neural biomarker, the persistence of the cortical subplate; a monoaminergic biomarker, noradrenergic and glutamatergic receptor overexpression; and a behavioural biomarker, the crying diathesis. By the time potential diagnostic signs are identified, from six months of age, ASD neuropathy is already entrenched. The International Society for Autism Research Special Interest Group has called for pre-emptive intervention, based upon rigorous theoretical frames which integrate the social communication and biological research literatures, with real world clinical translation and evaluation. This paper responds to that call. It synthesises heterogenous evidence concerning ASD in very early life from both biological and psychosocial research literatures with complexity science and evolutionary biology, to propose the theoretical framework for an integrated pre-emptive intervention. This paper hypothesises that environmental factors resulting from a mismatch between the infant’s environment of evolutionary adaptedness and culture initiate or unmask early motor and sensory-motor lesions, triggering a butterfly effect of multi-directional cascades of atypical developmental in the complex adaptive system of the parent and infant. Chronic SNS-HPA hyperarousal and disrupted parent-infant biobehavioural synchrony are the key biologic and behavioural mechanisms perpetuating these atypical developmental cascades. A clinical translation of this evidence is proposed, for application antenatally and in the first six months of life, as pre-emptive intervention for ASD.